Benign migratory glossitis with fissured tongue - M Goswami; A Verma; M Verma (Wolters Kluwer Medknow Publications, 2012)
Symptomatic benign migratory glossitis (BMG) or "geographic tongue" is a rare occurrence in pediatric dentistry though asymptomatic BMG is comparatively common. BMG presents itself as an ulcer-like region on the dorsum of the tongue, which may recur at different sites on the tongue, creating a migratory appearance. Asymptomatic cases usually resolve on their own but symptomatic cases need treatment. Fissured tongue is a benign condition characterized by deep grooves on the dorsum of the tongue and, in many cases, is associated with geographic tongue. This article presents a case of symptomatic geographic tongue with fissured tongue with a history of asthma.